The Effect of Padlet on Nursing Students' Drug Dose Calculation Skills - Şule Bıyık Bayram (Galenos Publishing House, 2024)
Objective: Nursing students attended distance learning due to the pandemic, which made it more difficult for them to learn how to calculate the right dose because drug dose calculation requires constant practice. This study investigated whether Padlet helped nursing students to learn how to calculate the right dose. Method: This study adopted a single-group pretest-posttest experimental research design. This study was conducted in the nursing department of a university in Turkey. The sample consisted of 42 first-year nursing students. Students participating in the research answered the "form for promotional features" and "drug dose calculation knowledge test" sent via Google Forms. Then, the researcher and participants shared and discussed the questions, pictures, and videos they prepared for drug dose calculation on Padlet for three weeks. At the end of three weeks, all participants filled out the knowledge test again. Number, percentage, and Wilcoxon test were used for data analysis. Results: It was determined that the students' test score average regarding drug dose calculation skills increased at a statistically significant level (p<0.05). It was determined that the students' knowledge level in calculating milligrams of drugs, converting drug units, and preparing scale and tablet type drugs increased significantly. Conclusion: At the end of the study, it was determined that different web 2.0 tools used in distance education enabled students to actively provide continuous education and increase their drug dose calculation skills. It is suggested that such applications are effective in extracurricular learning and can be used in applied subjects.